Sterically Frustrated Aromatic Enes with Various Colors Originating from Multiple Folded and Twisted Conformations in Crystal Polymorphs. Issue 28 (8th April 2022) - Nishiuchi, Tomohiko; Aibara, Seito; Yamakado, Takuya; Kimura, Ryo; Saito, Shohei; Sato, Hiroyasu; Kubo, Takashi
Abstract: Overcrowded ethylenes composed of 10‐methyleneanthrone and two bulky aromatic rings contain a twisted carbon–carbon double (C=C) bond as well as a folded anthrone unit. As such, they are unique frustrated aromatic enes (FAEs). Various colored crystals of these FAEs, obtained in different solvents, correspond to multiple metastable conformations of the FAEs with various twist and fold angles of the C=C bond, as well as various dihedral angles of attached aryl units with respect to the C=C bond. The relationships between color and these parameters associated with conformational features around the C=C bond were elucidated in experimental and computational studies. Owing to the fact that they are separated by small energy barriers, the variously colored conformations in the FAE crystal change in response to various external stimuli, such as mechanical grinding, hydrostatic pressure and thermal heating. Abstract : Crystal chameleons : Sterically frustrated aromatic enes (FAEs) composed of a 10‐methyleneanthrone and two bulky aromatic rings contain a twisted C=C bond as well as a folded anthrone unit. Their solid‐state energy landscapes show the presence of metastable intermediate crystals corresponding to conformations with different folds, twists and dihedral angles. Moreover, these FAE crystals have different absorption and emission colors from yellow to dark red that change in response to external stimuli, such as grinding, pressure, and heating.